Survival and disinfection of SARS-Cov-2 in environment and contaminated surface - Al-Gheethi, Adel; Noman, Efaq; Al-Maqtari, Qais; Almoheer, Reyad; Radin Mohamed, Radin Maya Saphira; Hamdan, Rafidah (Penerbit UTHM, 2020)
The detection of SARS-Cov-2 in the sewage and water resources has increased the awareness among the people about the possibility survival of SARS-Cov-2 in the environment and the potential to transmit into the human through food chain or water resources. Moreover, the surface contaminated by the virus need to be disinfected frequently by using an effective disinfectant, the current chapter discussed the efficiency of the most traditional treatment process of the sewage and wastewater, and their role in the elimination of the virus as well as the sterility assurance level concept. Moreover, the chemical disinfectant used currently and their temporary efficiency has been reviewed.